Geckos : The Animal Answer Guide - Bauer, Aaron M. (Book collections on Project MUSE., 2013)
Discover the biology, natural history, and diversity of geckos - the acrobatic little lizards made famous by a car insurance ad campaign. The author, a lizard biologist and gecko expert, answers deceptively simple questions with surprising and little-known facts. Readers can explore color photographs that reveal the natural wonder and beauty of the gecko form, as well as images of how geckos live in their natural habitats. Although written for nonexperts, this book also provides a carefully selected bibliography and a list of known species that will be of interest to herpetologists. -- Publisher's website.